Hollow resin particle-containing sheet
Hollow resin particles with controlled size and composition achieve high compressive strength and heat insulation by optimizing particle diameter, porosity, and volatile organic compound content, addressing the limitations of existing production methods.
Patent Information
- Application Number
- JP2023109704
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-03-30
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2039-03-25
AI Technical Summary
Existing methods struggle to produce hollow resin particles with high porosity, excellent heat resistance, and controlled particle size, leading to issues such as uneven particle diameters, low compressive strength, and poor heat insulation.
The development of hollow resin particles with a specific number average particle diameter of 0.1 to 9.0 μm, porosity of 70 to 99%, and volatile organic compound content of 5% by mass or less, utilizing a suspension polymerization method to control particle size and enhance mechanical properties.
The resulting particles exhibit high compressive strength, excellent heat insulation, and heat resistance, maintaining shape and performance under high temperatures.
Smart Images

Figure 0007619394000002 
Figure 0007619394000003 
Figure 0007619394000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to hollow resin particles having higher compressive strength and excellent heat insulating properties and heat resistance than conventional ones, and a sheet containing the same. [Background technology]
[0002] Hollow resin particles scatter light well and have low light transmittance compared to resin particles that do not substantially have voids inside, and therefore are widely used as organic pigments or hiding agents with excellent optical properties such as opacity and whiteness in water-based paints, paper coating compositions, and the like.
[0003] In applications such as water-based paints and paper coating compositions, it is desirable to increase the porosity of the hollow resin particles to be blended in order to improve the effects of weight reduction, heat insulation, opacity, etc. of the paints, paper coating compositions, etc. However, with conventionally known production methods, it has been difficult to produce hollow resin particles with high porosity and excellent heat resistance while controlling the particle size.
[0004] For example, Patent Document 1 discloses a method for producing heat-expandable microspheres essentially comprising a shell made of a thermoplastic resin and a blowing agent encapsulated therein, and describes that heat-expandable microspheres having a predetermined average particle size can be produced stably and efficiently without deteriorating the expansion performance.
[0005] Patent Document 2 also discloses that hollow resin particles are produced by (1) preparing a dispersed phase containing a vinyl monomer having no nitrile group, a phase separation promoter, a volatile solvent, a polymerization initiator, and a reaction catalyst, (2) preparing a continuous phase containing a solvent and a surfactant, (3) adding the dispersed phase to the continuous phase and then stirring the resulting mixture, (4) subjecting the resulting aqueous dispersion to a polymerization reaction under pressurized conditions, (5) depressurizing the mixture after the polymerization reaction at a temperature equal to or higher than the boiling point of the volatile solvent to obtain an aqueous dispersion, and (6) filtering and drying the resulting aqueous dispersion to obtain hollow resin particles. This document also discloses that the resin constituting the shell of the hollow resin particles is made of a vinyl monomer having no nitrile group, so that the nitrile group does not leave even at high temperatures and the strength of the shell is not easily reduced.
[0006] Patent Document 3 discloses a method for producing hollow polymer particles by polymerizing a dispersion of a hydrophilic monomer, a crosslinkable monomer and other monomers in the presence of an oily substance, and then removing the oily substance from the particles in liquid or air. Patent Document 4 discloses a method for producing hollow resin particles in which the organic solvent contained in the fine particles is removed in an aqueous medium to form hollow particles, thereby preventing the particles from collapsing. Patent Document 5 discloses hollow polymeric microparticles having a high content of crosslinkable monomers. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 6152237 [Patent Document 2] JP 2008-231241 A [Patent Document 3] Japanese Patent Application Publication No. 61-87734 [Patent Document 4] Patent No. 5727962 [Patent Document 5] Patent No. 4448930 Summary of the Invention [Problem to be solved by the invention]
[0008] Patent Document 1 states that it is preferable to contain a nitrile monomer as an essential component from the viewpoint of expansion performance. However, resin particles containing a nitrile monomer generally have poor heat resistance. In addition, the technology of Patent Document 1 has a problem that it is difficult to precisely control the particle size of the microspheres because the microspheres are expanded by foaming with a foaming agent and by a thermal expansion reaction. Patent Document 2 also describes that by decompressing at a temperature equal to or higher than the boiling point of the volatile solvent, the resin is pushed out by the pressure generated when the volatile solvent encapsulated in the resin evaporates, forming hollow resin particles. However, since the particles are expanded by decompressing while applying heat to the particles, there is a problem that the particle size of the obtained hollow resin particles is not uniform.
[0009] In the technology of Patent Document 3, when an attempt is made to produce hollow particles with a thin shell thickness by increasing the amount of oily substance, the shell has low strength and the particles are crushed when the oily substance is removed, resulting in the problem that particles with a high porosity cannot be obtained. The hollow particles produced by the method described in Patent Document 4 contain water, and when they are used as insulation materials or the like, a process for removing the water inside is required. At this stage, the particles tend to sink, resulting in a low porosity. In the case of the hollow polymeric microparticles described in Patent Document 5, there is a problem in that it is difficult to remove the hydrocarbon solvent from inside the particles even when treatment is carried out under high-temperature conditions for a long period of time.
[0010] In addition to the high porosity and excellent heat resistance described above, the hollow resin particles are required to have high compressive strength to maintain the hollow space of the particles. In addition, depending on the application, the hollow resin particles are also required to have excellent heat insulation properties by utilizing the poor heat transfer properties of the hollow space. An object of the present disclosure is to provide hollow resin particles having higher compressive strength than conventional ones and excellent heat insulating properties and heat resistance, and a sheet containing the hollow resin particles. [Means for solving the problem]
[0011] The present inventors have focused on the optimal particle size of hollow resin particles in order to increase the compressive strength. They have also examined the physical properties required to obtain hollow resin particles having better heat insulation and heat resistance than conventional ones. As a result, the present inventors have found that hollow resin particles having a specific number-average particle size, porosity, and amount of volatile organic compounds have high compressive strength, as well as excellent heat insulation and heat resistance.
[0012] That is, the sheet of the present disclosure is a sheet containing hollow resin particles, characterized in that the hollow resin particles have one or more hollow portions, have a number average particle size of 0.1 to 9.0 μm, a porosity of 70 to 99%, and contain volatile organic compounds in an amount of 5 mass% or less. The sheet of the present disclosure preferably has a thermal conductivity of 0.060 W / (m·K) or less. The sheet of the present disclosure preferably has a thickness change rate of 8.0% or less after heat treatment at 120° C. for 72 hours. In the present disclosure, the hollow resin particles preferably have a 10% compressive strength of 5.0 MPa or more. In the present disclosure, the repeating units constituting the resin contained in the hollow resin particles may contain a crosslinkable monomer unit. In the present disclosure, the content of the crosslinkable monomer unit may be 25 to 59 parts by mass when the repeating unit constituting the resin is taken as 100 parts by mass. In the present disclosure, the repeating units constituting the resin contained in the hollow resin particles may contain a hydrophilic monomer unit. In the present disclosure, the repeating units constituting the resin contained in the hollow resin particles may include a crosslinkable monomer unit, and the crosslinkable monomer unit may include at least one selected from the group consisting of a divinylbenzene monomer unit and an ethylene glycol dimethacrylate monomer unit. In the present disclosure, the hydrophilic monomer unit may include at least one selected from the group consisting of a carboxyl group-containing monomer unit and a hydroxyl group-containing monomer unit. In the present disclosure, the repeating units constituting the resin contained in the hollow resin particles may contain a monovinyl monomer unit.
[0013] In the present disclosure, the hollow resin particles may have a particle size distribution (volume average particle size (Dv) / number average particle size (Dn)) of 1.1 to 2.5. In the present disclosure, the hollow resin particles may have a shell, and the shell thickness may be 0.01 to 1.0 μm.
[0014] The sheet of the present disclosure may be a thermosensitive recording sheet. Effect of the Invention
[0015] According to the present disclosure as described above, the hollow resin particles have a specific number average particle size, porosity, and amount of volatile organic compounds, and therefore have high compressive strength and can exhibit excellent heat insulation and heat resistance. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic diagram showing one embodiment of a manufacturing method according to the present disclosure. FIG. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of a suspension in a suspension preparation step. [Figure 3A] 1 is a SEM image of hollow resin particles of Example 1. [Figure 3B] 2 is an SEM image of a cross section of a hollow resin particle of Example 1. [Figure 4] FIG. 1 is a schematic diagram showing a conventional dispersion for emulsion polymerization. [Diagram 5] FIG. 2 is a diagram illustrating a test sheet used in a test for evaluating a change in thickness of a sheet in a high-temperature environment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, in this disclosure, "hollow" means a state in which the presence of at least one selected from the group consisting of a liquid portion, a gas portion, and a mixture portion of liquid and gas can be confirmed inside the particle by a general observation method. In this disclosure, the "liquid portion" means a continuous portion filled with liquid. In this disclosure, the "gas portion" means a continuous portion filled with gas. In this disclosure, the "mixture portion of liquid and gas" means a continuous portion filled with liquid and gas. In the present disclosure, the term "hollow portion" refers to a portion of the inside of a particle that is hollow. Whether or not a particle has a hollow portion can be confirmed, for example, by SEM observation of the cross section of the target particle, or by TEM observation of the target particle as is. The resin shell of the particle may not have any communicating holes, and the "hollow portion" in the present disclosure may be isolated from the outside of the particle by the shell of the particle. The resin shell of the particle may have one or more communicating holes, and the "hollow portion" in the present disclosure may be connected to the outside of the particle via the communicating holes. In the present disclosure, the term "hollow resin particle precursor" refers to a particle whose hollow portion is filled with water or a mixture of water and gas, or an aqueous medium or a mixture of an aqueous medium and gas. In the present disclosure, the term "precursor composition" refers to a composition containing the hollow resin particle precursor. In the present disclosure, the term "hollow resin particles" refers to resin particles whose hollow portions are filled with gas.
[0018] 1. Hollow resin particles The hollow resin particles disclosed herein are hollow resin particles having one or more hollow portions, and are characterized by a number-average particle size of 0.1 to 9.0 μm, a porosity of 70 to 99%, and an amount of volatile organic compounds contained of 5 mass% or less.
[0019] As described above, the hollow resin particles are required to have high compressive strength, excellent heat insulation and heat resistance. In order to have these properties, it is necessary that the three physical parameters of the hollow resin particles, namely, the number average particle diameter, the porosity and the amount of volatile organic compounds of the hollow resin particles, are each within a specific numerical range. Below, an overview of the relationship between the above three physical parameters (number average particle diameter, porosity and the amount of volatile organic compounds) and the above three properties (compressive strength, heat insulation and heat resistance) will be described. The number-average particle diameter of hollow resin particles is a parameter related to their compressive strength and heat resistance. When the number-average particle diameter of hollow resin particles is sufficiently small, they are more difficult to crush than hollow resin particles with a larger number-average particle diameter, and therefore have high compressive strength. When the number-average particle diameter of hollow resin particles is sufficiently small, the surface area of the particles is also small, making them less susceptible to the external environment, and as a result, the particles can exhibit excellent heat resistance. Next, the porosity of hollow resin particles is a parameter related to their heat insulating properties. The hollow parts of hollow resin particles generally do not transmit heat as easily as if resin were present in those parts. Therefore, the higher the porosity, the higher the proportion of the hollow parts, and the better the heat insulating properties of the hollow resin particles. Next, the amount of volatile organic compounds contained in the hollow resin particles is a parameter related to the heat insulation and heat resistance. In the present disclosure, the term "volatile organic compounds contained in the hollow resin particles" refers to organic compounds having a boiling point of 400°C or less among the organic compounds contained in the hollow resin particles. Typical examples of volatile organic compounds include hydrocarbon solvents used in the manufacturing method described below and unreacted monomers, but are not necessarily limited to these typical examples. When the amount of volatile organic compounds in the hollow resin particles is sufficiently small, there is little risk that the volatile organic compounds will become a heat medium inside the hollow resin particles, and there is little risk that the heat transmitted to a part of the particles will propagate to the entire particle, so there is little risk of the heat insulation being reduced. In addition, when the amount of volatile organic compounds in the hollow resin particles is sufficiently small, even if the hollow resin particles are exposed to high temperatures, there is little risk that the hollow resin particles will expand due to the volatilization of the volatile organic compounds, so there is little risk of the heat resistance being reduced. In this way, the three physical property parameters of the hollow resin particles (number average particle size, porosity, and amount of volatile organic compounds) affect the above three characteristics (compressive strength, heat insulation, and heat resistance), respectively. The above three physical property parameters (number average particle diameter, porosity, and amount of volatile organic compounds) will be described in detail below in order.
[0020] The number average particle size of the hollow resin particles is usually 0.1 to 9.0 μm, preferably 0.2 to 8.0 μm, more preferably 0.4 to 6.0 μm, even more preferably 0.6 to 5.0 μm, and particularly preferably 0.8 to 4.0 μm. When the number-average particle diameter of the hollow resin particles is 0.1 μm or more, heat is not easily transferred to the entire hollow resin particles, so that the hollow resin particles can exhibit excellent heat insulation. When the number-average particle diameter of the hollow resin particles is 9.0 μm or less, the hollow resin particles are not easily crushed, so that they have high compressive strength. Furthermore, when the number-average particle diameter of the hollow resin particles is 9.0 μm or less, the surface area of the hollow resin particles is sufficiently small, so that the hollow resin particles are not easily affected by the external environment, so that the hollow resin particles can exhibit excellent heat resistance.
[0021] The particle size distribution of the hollow resin particles (volume average particle size (Dv) / number average particle size (Dn)) may be 1.1 to 2.5, 1.1 to 2.3, or 1.1 to 2.0. When the particle size distribution is 2.5 or less, particles with little variation in compressive strength properties and heat resistance between particles can be obtained. Furthermore, when a product such as a sheet described below is manufactured, for example, a product with a uniform thickness can be manufactured by the particle size distribution being 2.5 or less. The volume average particle diameter (Dv) and number average particle diameter (Dn) of the hollow resin particles can be determined by, for example, measuring the particle diameter of the hollow resin particles using a laser diffraction particle size distribution measuring device, calculating the number average and volume average, and using the obtained values as the number average particle diameter (Dn) and volume average particle diameter (Dv) of the particles. The particle size distribution is determined by dividing the volume average particle diameter by the number average particle diameter.
[0022] The porosity of the hollow resin particles is usually 70% or more, preferably 72% or more, more preferably 74% or more, even more preferably 78% or more, even more preferably 80% or more, and particularly preferably 82% or more. When the porosity of the hollow resin particles is 70% or more, the proportion of the hollow portion is high, so that the hollow resin particles have excellent heat insulating properties. From the viewpoint of maintaining the strength of the hollow resin particles, the porosity of the hollow resin particles may be 99% or less, or may be 95% or less.
[0023] The porosity of the hollow resin particle is calculated by dividing the apparent density D1 of the hollow resin particle by the true density D0, multiplying the result by 100, and subtracting the resultant value from 100. The method for measuring the apparent density D1 of hollow resin particles is as follows. 3 30 cm into a measuring flask 3 The hollow resin particles are filled into the measuring flask, and the mass of the filled hollow resin particles is precisely weighed. Next, the measuring flask filled with the hollow resin particles is precisely filled with isopropanol up to the marked line, while being careful not to introduce air bubbles. The mass of isopropanol added to the measuring flask is precisely weighed, and the apparent density D1 (g / cm) of the hollow resin particles is calculated based on the following formula (I): 3 ) to calculate Formula (I) Apparent density D1 = [mass of hollow resin particles] / (100 - [mass of isopropanol] ÷ [specific gravity of isopropanol at measurement temperature]) The apparent density D1 corresponds to the specific gravity of the entire hollow resin particle when the hollow portion is considered to be a part of the hollow resin particle.
[0024] The method for measuring the true density D0 of hollow resin particles is as follows. After crushing the hollow resin particles, 3 The measuring flask is filled with about 10 g of crushed pieces of hollow resin particles, and the mass of the crushed pieces is accurately weighed. Then, in the same manner as in the measurement of the apparent density, isopropanol is added to the measuring flask, and the mass of the isopropanol is accurately weighed, and the true density D0 (g / cm) of the hollow resin particles is calculated based on the following formula (II). 3 ) to calculate Formula (II) True density D0 = [mass of crushed pieces of hollow resin particles] / (100 - [mass of isopropanol] ÷ [specific gravity of isopropanol at measurement temperature]) The true density D0 corresponds to the specific gravity of only the shell portion of the hollow resin particle. As is clear from the above measurement method, the hollow portion is not considered to be part of the hollow resin particle when calculating the true density D0. The porosity of the hollow resin particle can be expressed as the ratio of the hollow portion to the specific gravity of the hollow resin particle.
[0025] The amount of volatile organic compounds contained in the hollow resin particles of the present disclosure is usually 5% by mass or less, preferably 4% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, even more preferably 1% by mass or less, and particularly preferably less than 1% by mass. When the amount of volatile organic compounds in the hollow resin particles is 5% by mass or less, the volatile organic compounds are unlikely to become a heat medium inside the hollow resin particles, and the heat transmitted to a part of the particle is unlikely to be transmitted to the whole particle, so that the insulation properties are unlikely to decrease. Also, when the amount of volatile organic compounds in the hollow resin particles is 5% by mass or less, even if the hollow resin particles are exposed to high temperatures, the hollow resin particles are unlikely to expand due to the volatilization of the volatile organic compounds, so that the heat resistance is unlikely to decrease or odors are unlikely to occur.
[0026] The method for measuring the amount of volatile organic compounds contained in hollow resin particles is as follows. Approximately 100 mg of hollow resin particles are placed in a 30 mL screw-top glass bottle and weighed accurately. Next, approximately 10 g of tetrahydrofuran (THF) is placed and weighed accurately. The mixture in the glass bottle is stirred with a stirrer for 1 hour to extract the volatile organic compounds contained in the hollow resin particles. The stirring is stopped, and the resin components of the hollow resin particles that are insoluble in THF are precipitated. A filter (Advantec, product name: Membrane Filter 25JP020AN) is attached to a syringe to filter the precipitate to obtain a sample liquid, which is then injected into a gas chromatograph (GC) for analysis. The amount of volatile organic compounds (mass%) per unit mass of the hollow resin particles is determined from the GC peak area and a calibration curve created in advance. The detailed analysis conditions are as follows.
[0027] (Analysis conditions) Equipment: GC-2010 (Shimadzu Corporation) Column: DB-5 (Agilent Technologies, Inc.) df=0.25μm 0.25mm ID x 30m Detector: FID Carrier gas: Nitrogen (linear velocity: 28.8 cm / sec) Inlet temperature: 200℃ Detector temperature: 250℃ Oven temperature: increase from 40°C to 230°C at a rate of 10°C / min, and hold at 230°C for 2 minutes. Sampling volume: 2μL
[0028] The compressive strength of the hollow resin particles can be measured, for example, by the following method. Using a microcompression tester (for example, MCTM-500, manufactured by Shimadzu Corporation), the 10% compression strength of the particles is measured under the following test conditions. (Test conditions) Indenter type: FLAT50 Objective lens magnification: 50 ·Load speed: 0.8924 mN / sec Although it depends on the application of the hollow resin particles, for example, if the compressive strength of the hollow resin particles is 5.0 MPa or more, the hollow resin particles can be evaluated as having high compressive strength. The heat resistance and heat insulation of the hollow resin particles may be evaluated using the hollow resin particles themselves, or may be evaluated using a sheet or the like produced using the hollow resin particles. The heat resistance evaluation and heat insulation evaluation of the hollow resin particles using a sheet will be described later.
[0029] As long as the above three physical property parameters (number average particle diameter, porosity, and amount of volatile organic compounds) satisfy the above conditions, the type of resin contained in the hollow resin particles and the type of repeating unit constituting the resin are not particularly limited. The resin contained in the hollow resin particles and its repeating unit will be described below.
[0030] The repeating units constituting the resin contained in the hollow resin particles may contain a monovinyl monomer unit. In this disclosure, the monovinyl monomer means a compound having one polymerizable vinyl functional group and other than the hydrophilic monomer described below. Polymerization of the monovinyl monomer produces a resin containing a monovinyl monomer unit. In this disclosure, the "monovinyl monomer" does not include the "crosslinkable monomer" described below unless otherwise specified. In the present disclosure, examples of monovinyl monomers include acrylic monovinyl monomers such as (meth)acrylates; aromatic vinyl monomers such as styrene, vinyl toluene, and α-methyl styrene; and monoolefin monomers such as ethylene, propylene, and butylene. In the present disclosure, (meth)acrylate is a general term including acrylate and methacrylate. Examples of (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, glycidyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate. The (meth)acrylate may be used alone or in combination of two or more. Of the above (meth)acrylates, at least one selected from the group consisting of butyl acrylate and methyl methacrylate is preferably used. In this way, by using a monomer that is relatively resistant to high temperature conditions, such as (meth)acrylate, the heat resistance of the resulting hollow resin particles can be improved compared to the case where, for example, a monomer having a nitrile group or the like is used.
[0031] The repeating units constituting the resin contained in the hollow resin particles may contain a hydrophilic monomer unit. In the present disclosure, the hydrophilic monomer means a compound that is soluble in water, and more specifically, a compound having a solubility in water of 1 (unit: g / 100 g-H2O) or more. The use of a hydrophilic monomer in the polymerization of the resin is particularly preferable in that the hollow resin particles obtained have fewer aggregates. The resin contained in the hollow resin particles may contain, as a hydrophilic monomer unit, for example, a carboxyl group-containing monomer unit, a hydroxyl group-containing monomer unit, an amide group-containing monomer unit, or a polyoxyethylene group-containing monomer unit. Among these, when the resin contains a carboxyl group-containing monomer unit, it is preferable in terms of obtaining particles with high heat resistance. In addition, when the resin contains a hydroxyl group-containing monomer unit, it is preferable in terms of the effect of using a hydrophilic monomer, that is, the effect of using a hydrophilic monomer in the polymerization of the resin, particularly the effect of obtaining fewer aggregates of hollow resin particles. Examples of the carboxyl group-containing monomer include (meth)acrylic acid monomer, maleic acid monomer, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, etc. In the present disclosure, (meth)acrylic acid is a general term including acrylic acid and methacrylic acid. When the carboxyl group-containing monomer is used in combination with the above-mentioned (meth)acrylate, the preferred mass ratio is carboxyl group-containing monomer:(meth)acrylate=100:0 to 10:90, the more preferred mass ratio is carboxyl group-containing monomer:(meth)acrylate=100:0 to 20:80, the even more preferred mass ratio is carboxyl group-containing monomer:(meth)acrylate=100:0 to 30:70, and the particularly preferred mass ratio is carboxyl group-containing monomer:(meth)acrylate=100:0 to 35:65. When (meth)acrylic acid is used as the carboxyl group-containing monomer, the preferred mass ratio is the same as above. That is, when (meth)acrylic acid is used in combination with the above-mentioned (meth)acrylate, the preferred mass ratio is (meth)acrylic acid:(meth)acrylate=100:0-10:90, the more preferred mass ratio is (meth)acrylic acid:(meth)acrylate=100:0-20:80, the further more preferred mass ratio is (meth)acrylic acid:(meth)acrylate=100:0-30:70, and the particularly preferred mass ratio is (meth)acrylic acid:(meth)acrylate=100:0-35:65. Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl acrylate monomer, 2-hydroxyethyl methacrylate monomer, 2-hydroxypropyl acrylate monomer, 2-hydroxypropyl methacrylate monomer, and 4-hydroxybutyl acrylate monomer. Examples of the amide group-containing monomer include an acrylamide monomer and a dimethylacrylamide monomer. Examples of the polyoxyethylene group-containing monomer include a methoxypolyethylene glycol acrylate monomer and a methoxypolyethylene glycol methacrylate monomer.
[0032] The repeating units constituting the resin contained in the hollow resin particles may contain a crosslinkable monomer unit. In the present disclosure, the crosslinkable monomer means a compound having two or more polymerizable functional groups. The use of the crosslinkable monomer can improve the mechanical properties of the resulting copolymer shell. In addition, since the crosslinkable monomer has a plurality of polymerizable functional groups, the above-mentioned monovinyl monomer and hydrophilic monomer can be linked to each other, and in particular, the heat resistance of the resulting hollow resin particles can be improved. The crosslinkable monomer is not particularly limited as long as it has two or more polymerizable functional groups. Examples of the crosslinkable monomer include aromatic divinyl compounds such as divinylbenzene, divinylnaphthalene, diallyl phthalate, and derivatives thereof; ester compounds in which a compound having two or more hydroxyl groups or carboxyl groups is ester-bonded to a compound having two or more carbon-carbon double bonds, such as allyl (meth)acrylate, ethylene glycol di(meth)acrylate, and diethylene glycol di(meth)acrylate; and other divinyl compounds such as N,N-divinylaniline and divinyl ether; among which divinylbenzene and ethylene glycol di(meth)acrylate are preferred. The monomer may contain other polymerizable monomers in addition to the monovinyl monomer, the hydrophilic monomer and the crosslinkable monomer.
[0033] When the repeating units constituting the resin are taken as 100 parts by mass, the content of the crosslinkable monomer units may be 25 to 59 parts by mass, preferably 30 to 57 parts by mass, and more preferably 35 to 55 parts by mass. When the content of the crosslinkable monomer units is 25 to 59 parts by mass, there is no risk of the obtained hollow resin particles being dented, so that the porosity of the hollow resin particles can be maintained high, and there is little risk of volatile organic compounds remaining in the hollow resin particles. The content ratio of the crosslinkable monomer unit can be obtained, for example, by calculating the ratio of the crosslinkable monomer supplied to the polymerization reaction from the amount of the crosslinkable monomer charged at the time of polymerization and the remaining amount of the crosslinkable monomer at the end of polymerization.
[0034] In addition to the above-mentioned resins, the resin constituting the hollow resin particles may be, for example, a urethane resin or an epoxy resin. Among these resins, the resin constituting the hollow resin particles may be, for example, a urethane resin because of its excellent heat insulating properties, or an epoxy resin because of its expected high compressive strength.
[0035] The shape of the hollow resin particles is not particularly limited as long as a hollow portion is formed inside, and examples thereof include a spherical shape, an oval spherical shape, an irregular shape, etc. Among these, a spherical shape is preferred from the viewpoint of ease of production. The inside of the particle has one or more hollow parts. The inside of the particle may be porous as long as the hollow parts are secured. In order to maintain a good balance between the high porosity of the hollow resin particle and the compressive strength of the hollow resin particle, the inside of the particle preferably has 5 or less hollow parts, more preferably 3 or less hollow parts, even more preferably 2 or less hollow parts, and particularly preferably only 1 hollow part.
[0036] The average circularity of the hollow resin particles may be 0.950 to 0.995, 0.970 to 0.995, or 0.980 to 0.995. In the present disclosure, the circularity is defined as the perimeter of a circle having the same projected area as the particle image divided by the perimeter of the projected image of the particle. The average circularity in the present disclosure is used as a simple method for quantitatively expressing the shape of the hollow resin particles, and is an index showing the degree of unevenness of the hollow resin particles. The average circularity is 1 when the hollow resin particles are perfectly spherical, and the more complex the surface shape of the hollow resin particles, the smaller the value.
[0037] When the hollow resin particles of the present disclosure have a shell, the shell thickness may be 0.01 to 1.0 μm, 0.02 to 0.95 μm, or 0.05 to 0.90 μm. When the shell thickness is 0.01 μm or more, the hollow resin particles can maintain a high compressive strength sufficient to maintain their shape, whereas when the shell thickness is 1.0 μm or less, a large hollow space can be secured inside the hollow resin particles. The method for measuring the shell thickness of hollow resin particles is as follows. First, 20 target hollow resin particles are selected, and the cross sections of the hollow resin particles are observed using an SEM. Next, the shell thickness of each of the 20 hollow resin particles is measured from the SEM images of the particle cross sections. The average of these thicknesses is taken as the shell thickness of the hollow resin particles.
[0038] An example of the shape of a hollow resin particle is a bag made of a thin film and inflated with gas, and a cross-sectional view of the hollow resin particle is shown in Fig. 1. In this example, the outermost layer of the hollow resin particle is formed of a single thin film, and the inside is filled with gas. The shape of the hollow resin particles can be confirmed, for example, by SEM or TEM. The internal shape of the hollow resin particles can be confirmed by SEM or TEM after cutting the particles into slices by a known method.
[0039] The hollow resin particles may be used, for example, as an undercoat material for thermal paper. In general, undercoat materials are required to have heat insulation and shock-absorbing properties (cushioning properties), and are also required to have heat resistance suitable for thermal paper applications. The hollow resin particles of the present disclosure can meet these requirements due to their high porosity, hollow shape that is not easily crushed, specific number-average particle size, and high heat resistance. Furthermore, hollow resin particles are useful, for example, as plastic pigments having excellent gloss, hiding power, etc. Furthermore, hollow resin particles obtained by encapsulating useful components such as fragrances, medicines, agricultural chemicals, ink components, etc., by means of immersion treatment, reduced pressure or pressurized immersion treatment, etc., can be used for various purposes depending on the components contained therein. Specific applications of the hollow resin particles include, for example, thermal recording materials, fillers, scattering agents, paints, insulating materials, and the like, but are not necessarily limited to these examples.
[0040] 2. Manufacturing method of hollow resin particles The method for producing hollow resin particles is not particularly limited as long as it can produce hollow resin particles that satisfy the above-mentioned conditions of number average particle diameter, porosity, and amount of volatile organic compounds. Hereinafter, one embodiment of the method for producing hollow resin particles will be described, but the method for producing hollow resin particles disclosed herein is not necessarily limited to the following embodiment.
[0041] One embodiment of the method for producing hollow resin particles includes: A step of preparing a mixed liquid containing at least one monomer selected from the group consisting of monovinyl monomers and hydrophilic monomers, a crosslinkable monomer, an oil-soluble polymerization initiator, a hydrocarbon solvent, a suspension stabilizer, and an aqueous medium (mixed liquid preparation step); a step of preparing a suspension in which monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium by suspending the mixed liquid (suspension preparation step); a step of polymerizing the suspension to prepare a precursor composition containing a hollow resin particle precursor encapsulating a hydrocarbon-based solvent (polymerization step); a step of obtaining a hollow resin particle precursor by performing solid-liquid separation of the precursor composition (solid-liquid separation step); a step of removing the hydrocarbon solvent contained in the hollow resin particle precursor in air to obtain hollow resin particles (solvent removal step); Includes.
[0042] As described above, this embodiment includes (1) a mixed solution preparation step, (2) a suspension preparation step, (3) a polymerization step, (4) a solid-liquid separation step, and (5) a solvent removal step. The steps of this embodiment are not limited to these five steps. FIG. 1 is a schematic diagram showing this embodiment. (1) to (5) in FIG. 1 correspond to the above-mentioned steps (1) to (5). The white arrows between the figures indicate the order of the steps. Note that FIG. 1 is merely a schematic diagram for explanation, and the method for producing hollow resin particles of the present disclosure is not limited to that shown in FIG. 1. Furthermore, the structure, dimensions, and shape of the materials used in the method for producing hollow resin particles of the present disclosure are not limited to the structure, dimensions, and shape of the various materials in FIG. 1. 1(1) is a schematic diagram showing one embodiment of the mixed liquid in the mixed liquid preparation step. As shown in this figure, the mixed liquid contains an aqueous medium 1 and a low-polarity material 2 dispersed in the aqueous medium 1. Here, the low-polarity material 2 refers to a material that has low polarity and is difficult to mix with the aqueous medium 1, such as a monovinyl monomer or a hydrocarbon solvent. 1(2) is a schematic diagram showing one embodiment of a suspension in a suspension preparation step. The suspension contains an aqueous medium 1 and micelles 10 (monomer droplets) dispersed in the aqueous medium 1. The micelle 10 is formed by surrounding an oil-soluble monomer composition 4 (containing an oil-soluble polymerization initiator 5, etc.) with a surfactant 3. 1(3) is a schematic diagram showing one embodiment of the precursor composition after the polymerization step. The precursor composition contains an aqueous medium 1 and a hollow resin particle precursor 20 dispersed in the aqueous medium 1. The hollow resin particle precursor 20 is formed by polymerization of a monovinyl monomer or the like in the micelle 10, and encapsulates a hydrocarbon solvent 7 inside a shell 6. 1(4) is a schematic diagram showing one embodiment of the hollow resin particle precursor after the solid-liquid separation step, in which the aqueous medium 1 is separated from the state shown in (3) above. 1 (5) is a schematic diagram showing one embodiment of hollow resin particles after the solvent removal step. This (5) shows the state after removing the hydrocarbon solvent 7 from the state of (4) above. As a result, hollow resin particles 100 having a hollow portion 8 inside a shell 6 are obtained. The above five steps and other steps will be described below in order.
[0043] (1) Mixed liquid preparation process This process is a process for preparing a mixed liquid containing (A) at least one monomer selected from the group consisting of monovinyl monomers and hydrophilic monomers, (B) a crosslinkable monomer, (C) an oil-soluble polymerization initiator, (D) a hydrocarbon solvent, (E) a suspension stabilizer, and an aqueous medium. Among these, (A) monovinyl monomer and hydrophilic monomer, and (B) crosslinkable monomer are as explained in the above "1. Hollow resin particles". The mixed liquid may contain other polymerizable monomers in addition to (A) at least one monomer selected from the group consisting of monovinyl monomer and hydrophilic monomer, and (B) crosslinkable monomer, as explained in the above "1. Hollow resin particles".
[0044] (C) Oil-soluble polymerization initiator In this embodiment, a suspension polymerization method using an oil-soluble polymerization initiator is used instead of an emulsion polymerization method using a water-soluble polymerization initiator. The advantages of using the suspension polymerization method will be described in detail in "(2) Suspension preparation step". The oil-soluble polymerization initiator is not particularly limited as long as it is lipophilic and has a solubility in water of 0.2 (unit: g / 100 g-H2O) or less. Examples of the oil-soluble polymerization initiator include benzoyl peroxide, lauroyl peroxide, t-butyl peroxide-2-ethylhexanoate, 2,2'-azobis(2,4-dimethylvaleronitrile), and azobisisobutyronitrile.
[0045] When the total mass of (A) at least one monomer selected from the group consisting of monovinyl monomers and hydrophilic monomers, and (B) crosslinkable monomer is 100 parts by mass, the content of (C) oil-soluble polymerization initiator is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, and even more preferably 1 to 5 parts by mass. When the content of (C) oil-soluble polymerization initiator is 0.1 parts by mass or more, the polymerization reaction is likely to proceed sufficiently. On the other hand, when the content of (C) oil-soluble polymerization initiator is 10 parts by mass or less, there is little risk of the oil-soluble polymerization initiator remaining after the polymerization reaction is completed, and as a result, there is little risk of an unexpected side reaction proceeding.
[0046] (D) Hydrocarbon solvents The hydrocarbon solvent in this embodiment serves to form hollow spaces inside the particles. In the suspension preparation step described below, a suspension is obtained in which monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium. In the suspension preparation step, phase separation occurs in the monomer droplets, and as a result, the hydrocarbon solvent with low polarity tends to collect inside the monomer droplets. Ultimately, the monomer droplets are distributed with the hydrocarbon solvent inside and materials other than the hydrocarbon solvent on the periphery according to their respective polarities. Then, in the polymerization step described later, a precursor composition containing hollow resin particle precursors encapsulating a hydrocarbon-based solvent is obtained. That is, the hydrocarbon-based solvent is collected inside the particles, and hollows made of the hydrocarbon-based solvent are formed inside the obtained polymer particles (hollow resin particle precursors).
[0047] The type of the hydrocarbon solvent is not particularly limited, and examples of the hydrocarbon solvent include relatively volatile solvents such as benzene, toluene, xylene, butane, pentane, hexane, heptane, and cyclohexane.
[0048] The hydrocarbon solvent used in this embodiment preferably has a relative dielectric constant of 3 or less at 20° C. The relative dielectric constant is one of the indices that indicate the polarity of a compound. When the relative dielectric constant of the hydrocarbon solvent is sufficiently small, 3 or less, it is considered that phase separation proceeds quickly in the monomer droplets, and hollow spaces are easily formed. Examples of solvents with a dielectric constant of 3 or less at 20°C are as follows. The value in parentheses is the dielectric constant value. Heptane (1.9), cyclohexane (2.0), benzene (2.3), toluene (2.4). For the relative dielectric constant at 20°C, values described in known documents (for example, "Chemical Handbook Basic Edition" edited by the Chemical Society of Japan, revised 4th edition, Maruzen Co., Ltd., published on September 30, 1993, pages II-498 to II-503) and other technical information can be referenced. Examples of methods for measuring the relative dielectric constant at 20°C include a relative dielectric constant test performed in accordance with JISC 2101:1999, Section 23, at a measurement temperature of 20°C.
[0049] The hydrocarbon-based solvent used in the present embodiment may be a hydrocarbon compound having 5 to 7 carbon atoms. The hydrocarbon compound having 5 to 7 carbon atoms is easily encapsulated in the hollow resin particle precursor during the polymerization step, and can be easily removed from the hollow resin particle precursor during the solvent removal step. Among these, the hydrocarbon-based solvent is preferably a hydrocarbon compound having 6 carbon atoms.
[0050] When the total mass of (A) at least one monomer selected from the group consisting of monovinyl monomers and hydrophilic monomers, and (B) crosslinkable monomer is taken as 100 parts by mass, the content of (D) hydrocarbon solvent is preferably 100 to 900 parts by mass, more preferably 150 to 700 parts by mass, and even more preferably 200 to 500 parts by mass. When the content of (D) hydrocarbon solvent is 100 parts by mass or more, the porosity of the obtained hollow resin particles is less likely to be small. On the other hand, when the content of (D) hydrocarbon solvent is 900 parts by mass or less, the mechanical properties of the obtained hollow resin particles are often excellent, and there is less possibility that the hollowness cannot be maintained.
[0051] (E) Suspension stabilizer The suspension stabilizer is an agent that stabilizes the suspended state in the suspension in the suspension polymerization method described below. The suspension stabilizer may contain a surfactant, which is a material that forms micelles encapsulating at least one monomer selected from the group consisting of monovinyl monomers and hydrophilic monomers, a crosslinkable monomer, an oil-soluble polymerization initiator, and a hydrocarbon solvent in the suspension polymerization method described below. As the surfactant, any of cationic surfactants, anionic surfactants, and nonionic surfactants can be used, and they can also be used in combination. Among these, anionic surfactants and nonionic surfactants are preferred, and anionic surfactants are more preferred. Examples of the anionic surfactant include sodium dodecylbenzenesulfonate, sodium lauryl sulfate, sodium dialkylsulfosuccinate, and formalin condensate salts of naphthalenesulfonic acid. Examples of the nonionic surfactant include polyoxyethylene alkyl ethers, polyoxyethylene alkyl esters, and polyoxyethylene sorbitan alkyl esters. Examples of the cationic surfactant include didecyldimethylammonium chloride and stearyltrimethylammonium chloride. The suspension stabilizer may contain a poorly water-soluble inorganic compound, a water-soluble polymer, or the like.
[0052] When the total mass of (A) at least one monomer selected from the group consisting of monovinyl monomers and hydrophilic monomers, (B) crosslinkable monomer, (C) oil-soluble polymerization initiator, and (D) hydrocarbon solvent is taken as 100 parts by mass, the content of (E) suspension stabilizer is preferably 0.1 to 3 parts by mass, more preferably 0.2 to 2 parts by mass, and even more preferably 0.3 to 1 part by mass. When the content of (E) suspension stabilizer is 0.1 parts by mass or more, micelles are easily formed in the aqueous medium. On the other hand, when the content of (E) suspension stabilizer is 3 parts by mass or less, a decrease in productivity due to an increase in foaming is unlikely to occur in the process of removing the hydrocarbon solvent.
[0053] (F)Other In this embodiment, the aqueous medium means any one of water, a hydrophilic solvent, or a mixture of water and a hydrophilic solvent. The hydrophilic solvent in this embodiment is not particularly limited as long as it is sufficiently miscible with water and does not cause phase separation. Examples of the hydrophilic solvent include alcohols such as methanol and ethanol, tetrahydrofuran (THF), and dimethyl sulfoxide (DMSO). Among aqueous media, water is preferably used due to its high polarity. When using a mixture of water and a hydrophilic solvent, it is important that the polarity of the entire mixture is not too low from the viewpoint of forming monomer droplets. For example, the mixture ratio (mass ratio) of water to hydrophilic solvent may be water:hydrophilic solvent=99:1 to 50:50, etc.
[0054] The mixed liquid prepared in this step is a composition in a state in which the materials (A) to (E) and the aqueous medium are simply mixed and appropriately stirred. In this mixed liquid, the oil phase containing the materials (A) to (D) is dispersed in the aqueous medium with particle sizes of about several mm. The dispersion state of these materials in the mixed liquid can be observed with the naked eye depending on the type of material.
[0055] In this step, a mixed solution may be prepared by mixing an oil phase containing (A) at least one monomer selected from the group consisting of monovinyl monomers and hydrophilic monomers, (B) a crosslinkable monomer, (C) an oil-soluble polymerization initiator, and (D) a hydrocarbon solvent, and containing 25 to 59 parts by mass of the crosslinkable monomer (B) when the total mass of (A) at least one monomer selected from the group consisting of monovinyl monomers and hydrophilic monomers, and (B) the crosslinkable monomer is 100 parts by mass, and an aqueous phase containing (E) a suspension stabilizer and an aqueous medium. By mixing the oil phase and the aqueous phase in this way, particles with a uniform composition can be formed.
[0056] (2) Suspension preparation process This step is a step of preparing a suspension in which monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium by suspending the above-mentioned mixed liquid. In the suspension prepared in this step, monomer droplets containing the above materials (A) to (D) and having a particle size of about 0.1 μm to 9 μm are uniformly dispersed in the aqueous medium. Such monomer droplets are difficult to observe with the naked eye, but can be observed using a known observation device such as an optical microscope.
[0057] As described above, in this embodiment, the suspension polymerization method is adopted instead of the emulsion polymerization method. Therefore, the advantages of the suspension polymerization method and the use of an oil-soluble polymerization initiator will be described below in comparison with the emulsion polymerization method. Fig. 4 is a schematic diagram showing a dispersion liquid for emulsion polymerization, in which a micelle 60 is shown in a schematic cross section. 4 shows a state in which micelles 60, micelle precursors 60a, monomers 53a dissolved in the solvent, and a water-soluble polymerization initiator 54 are dispersed in an aqueous medium 51. The micelles 60 are formed by surrounding an oil-soluble monomer composition 53 with a surfactant 52. The monomer composition 53 contains monomers and the like that are raw materials for a polymer, but does not contain a polymerization initiator. On the other hand, the micelle precursor 60a is an aggregate of the surfactant 52, but does not contain a sufficient amount of the monomer composition 53. The micelle precursor 60a grows into a micelle 60 by incorporating the monomer 53a dissolved in the solvent and by procuring a part of the monomer composition 53 from other micelles 60, etc. The water-soluble polymerization initiator 54 penetrates into the micelles 60 and the micelle precursors 60a while diffusing in the aqueous medium 51, and promotes the growth of oil droplets inside them. Therefore, in the emulsion polymerization method, although each micelle 60 is monodispersed in the aqueous medium 51, the particle size of the micelles 60 is expected to grow to several hundreds of nm.
[0058] Fig. 2 is a schematic diagram showing one embodiment of the suspension in this step. Micelle 10 in Fig. 2 is a schematic diagram showing a cross section thereof. Note that Fig. 2 is merely a schematic diagram, and the suspension in this embodiment is not necessarily limited to that shown in Fig. 2. A part of Fig. 2 corresponds to (2) in Fig. 1 described above. 2 shows micelles 10 and monomers 4a (including monovinyl monomers, crosslinkable monomers, etc.) dispersed in an aqueous medium 1. The micelles 10 are formed by surrounding an oil-soluble monomer composition 4 with a surfactant 3. The monomer composition 4 contains an oil-soluble polymerization initiator 5, as well as monomers (including monovinyl monomers, crosslinkable monomers, etc.) and a hydrocarbon solvent (none of which are shown). 2, in this process, fine oil droplets containing a monomer composition 4 are formed in advance inside micelles 10, and then polymerization initiation radicals are generated in the fine oil droplets by an oil-soluble polymerization initiator 5. Therefore, it is possible to produce hollow resin particle precursors with the desired particle size without causing the fine oil droplets to grow too much. In addition, as can be seen by comparing suspension polymerization (FIG. 2) with emulsion polymerization (FIG. 4), in suspension polymerization (FIG. 2), there is no opportunity for the oil-soluble polymerization initiator 5 to come into contact with the monomer 4a dispersed in the aqueous medium 1. Therefore, by using an oil-soluble polymerization initiator, it is possible to prevent the generation of excess polymer particles in addition to the intended hollow resin particles.
[0059] A typical example of this process is shown below. The above materials (A) to (E) and a mixed liquid containing an aqueous medium are suspended to form monomer droplets. The method for forming the monomer droplets is not particularly limited, but may be performed using a device capable of strong stirring, such as an (in-line type) emulsifying disperser (manufactured by Pacific Machinery Works, product name: Milder) or a high-speed emulsifying disperser (manufactured by Primix Corporation, product name: TK Homomixer MARK II type). As described above, in this process, phase separation occurs in the monomer droplets, and the hydrocarbon solvent with low polarity tends to collect inside the monomer droplets. As a result, the obtained monomer droplets have the hydrocarbon solvent distributed inside and materials other than the hydrocarbon solvent distributed around the periphery.
[0060] A variation of this process is shown below. First, an oil phase containing the above materials (A) to (D) and an aqueous phase containing material (E) and an aqueous medium are prepared. In the oil phase, it is preferable to prepare the content of the crosslinkable monomer (B) in an amount of 25 to 59 parts by mass when the total mass of the at least one monomer selected from the group consisting of (A) monovinyl monomers and hydrophilic monomers, and the crosslinkable monomer (B) is taken as 100 parts by mass. Next, a suspension is prepared by a membrane emulsification method. The membrane emulsification method is a method in which a suspension in which microdroplets of the dispersed phase are dispersed in a continuous phase is obtained by extruding the dispersed phase liquid through the pores of a porous membrane into the continuous phase. Here, the dispersed phase means the liquid phase dispersed as microdroplets, and the continuous phase means the liquid phase surrounding the dispersed phase droplets. In this embodiment, any of the direct membrane emulsification method and the membrane emulsification method accompanied by preliminary emulsification can be adopted as long as the membrane emulsification method uses the oil phase as the dispersed phase and the aqueous phase as the continuous phase. The membrane emulsification method uses a membrane emulsification system (e.g., model number: MN-20, manufactured by SPG Techno Co., Ltd.) and a membrane having a specific pore size. Examples of porous membranes that can be used in the membrane emulsification method include inorganic porous membranes such as shirasu porous glass membranes (SPG membranes) and organic porous membranes such as PTFE membranes. The pore size of the porous membrane in the membrane emulsification method determines the particle size of the resulting microdroplets. Although it depends on the components in the dispersed phase, the particle size of the microdroplets affects the number-average particle size of the resulting hollow resin particles, so the selection of the pore size of the porous membrane is important. For example, when using a Shirasu porous glass membrane (SPG membrane), the pore size of the membrane is preferably selected to be 0.1 to 4.0 μm, more preferably 0.2 to 3.5 μm, and even more preferably 0.3 to 3.0 μm. A suspension is prepared by performing membrane emulsification using a membrane emulsification system and a porous membrane, with the oil phase as the dispersed phase and the aqueous phase as the continuous phase. The suspension preparation process in this embodiment is not limited to the typical examples and modified examples described above.
[0061] (3) Polymerization process This step is a step of preparing a precursor composition containing hollow resin particle precursors encapsulating a hydrocarbon solvent by polymerizing the above-mentioned suspension. Here, the hollow resin particle precursors are particles formed by copolymerization of at least one monomer selected from the group consisting of at least the above-mentioned monovinyl monomers and hydrophilic monomers with a crosslinkable monomer. The polymerization method is not particularly limited, and for example, a batch method, a semi-continuous method, a continuous method, etc. can be used. The polymerization temperature is preferably 40 to 80° C., more preferably 50 to 70° C. The polymerization reaction time is preferably 1 to 20 hours, more preferably 2 to 15 hours. Since the monomer droplets containing the hydrocarbon-based solvent therein are used, as described above, hollow spaces filled with the hydrocarbon-based solvent are formed inside the hollow resin particle precursor.
[0062] (4) Solid-liquid separation process This step is a step of obtaining hollow resin particle precursors by subjecting the above-mentioned precursor composition to solid-liquid separation. When removing a hydrocarbon-based solvent contained in particles in a slurry containing an aqueous medium, there is a problem that the resulting hollow resin particles will be crushed unless the same volume of water as the hydrocarbon-based solvent that has escaped from the particles enters the particles. One possible way to prevent this is to adjust the pH of the slurry to 7 or higher, swell the shell of the particles with an alkali, and then remove the hydrocarbon solvent. In this case, the shell of the particle acquires flexibility, and the hydrocarbon solvent inside the particle is quickly replaced by water, resulting in particles containing water.
[0063] The method for solid-liquid separation of the precursor composition is not particularly limited as long as it is a method for separating a solid content containing the hollow resin particle precursor from a liquid content containing an aqueous medium without removing the hydrocarbon solvent contained in the hollow resin particle precursor, and a known method can be used. Examples of the solid-liquid separation method include a centrifugation method, a filtration method, and a static separation method. Among these, the centrifugation method or the filtration method may be used, and the centrifugation method may be adopted from the viewpoint of ease of operation. After the solid-liquid separation step, any step such as a pre-drying step may be carried out before carrying out the solvent removal step described below. Examples of the pre-drying step include a step of pre-drying the solid content obtained after the solid-liquid separation step using a drying device such as a dryer or a drying tool such as a hand dryer.
[0064] (5) Solvent removal process This step is a step of obtaining hollow resin particles by removing the hydrocarbon solvent contained in the hollow resin particle precursor in air.
[0065] In this process, "in the air" is not limited to an environment in which absolutely no liquid exists outside the hollow resin particle precursor, which is the strict meaning of "in the air," but means an environment in which only a very small amount of liquid exists outside the hollow resin particle precursor, to the extent that it does not affect the removal of the hydrocarbon solvent. "In the air" can also be expressed as a state in which the hollow resin particle precursor does not exist in a slurry, or a state in which the hollow resin particle precursor exists in a dry powder.
[0066] As shown in Examples 1 to 5 described below, the hollow resin particles maintain their spherical shape after being vacuum-dried in the solvent removal step and then returned to normal pressure. This is considered to be evidence that the gas permeability of the shell itself is relatively high. It is generally known that nylon, ethylene vinyl alcohol (EVOH), etc., have improved gas permeability under high humidity. This is understood to be due to the fact that these polymers are plasticized by water molecules, resulting in increased polymer mobility. However, since the hollow resin particles of the present disclosure are considered to have a high degree of crosslinking, it is presumed that the plasticization effect due to the action of the aqueous medium is small. Therefore, it is considered that the gas permeability of the shell of the hollow resin particles in the present disclosure is due to the inherent properties of the polymer that constitutes the shell.
[0067] The method for removing the hydrocarbon solvent in the hollow resin particle precursor in air is not particularly limited, and any known method can be used, such as reduced pressure drying, heat drying, air flow drying, or a combination of these methods. In particular, when the heat drying method is used, the heating temperature must be equal to or higher than the boiling point of the hydrocarbon solvent and equal to or lower than the maximum temperature at which the shell structure of the hollow resin particles does not collapse. Therefore, depending on the composition of the shell in the hollow resin particle precursor and the type of the hydrocarbon solvent, the heating temperature may be, for example, 50 to 150°C, 60 to 130°C, or 70 to 100°C. By the drying operation in air, the hydrocarbon solvent inside the hollow resin particle precursor is replaced by the external gas, resulting in hollow resin particles whose hollow portions are filled with gas.
[0068] The drying atmosphere is not particularly limited and can be appropriately selected depending on the application of the hollow resin particles. Examples of the drying atmosphere include air, oxygen, nitrogen, argon, etc. In addition, hollow resin particles with a temporary vacuum inside can be obtained by filling the inside of the hollow resin particles with a gas and then drying them under reduced pressure.
[0069] (6)Other As a step other than the above steps (1) to (5), for example, a step of replacing the gas inside the hollow resin particles with another gas or liquid is considered. By such a replacement, it is possible to change the environment inside the hollow resin particles, selectively confine molecules inside the hollow resin particles, or modify the chemical structure inside the hollow resin particles according to the application.
[0070] 3. Sheets The sheet of the present disclosure is characterized by containing the hollow resin particles. The sheet of the present disclosure may be composed of only hollow resin particles, or may contain hollow resin particles and other materials such as a binder, etc. In addition, the sheet of the present disclosure may be a single-layer sheet containing hollow resin particles, or a multi-layer sheet formed by laminating a layer containing hollow resin particles and one or more other layers.
[0071] The shape, area, and thickness of the sheet of the present disclosure can be freely designed depending on the application. Among these, the thickness of the sheet of the present disclosure may be, for example, 10 μm to 1 mm. The sheet of the present disclosure may be produced by a conventionally known method. For example, the sheet of the present disclosure can be produced by the following method. First, a mixed liquid containing hollow resin particles, a binder such as polyvinyl alcohol (PVA), and a surfactant is applied onto a substrate such as a PET substrate. At this time, the amount of the mixed liquid applied is adjusted so that the average thickness of only the layer containing the hollow resin particles (average thickness excluding the substrate) after drying the mixed liquid becomes a desired thickness. A sheet is produced on the substrate by appropriately drying the substrate after coating with the mixed liquid. The obtained multilayer sheet may be used for various applications described later, or a single layer sheet obtained by peeling it off from the substrate may be used for various applications described later.
[0072] The following describes the evaluation of the heat insulation property and the heat resistance of the sheet using the hollow resin particles. The heat insulating property of the sheet using hollow resin particles can be evaluated, for example, by the thermal conductivity of the sheet. The method for measuring the thermal conductivity of the sheet is as follows. Using a rapid thermal conductivity meter (e.g., QTM-500, manufactured by Kyoto Electronics Manufacturing Co., Ltd., etc.) and thin film measurement software (e.g., SOFT-QTM5W, manufactured by Kyoto Electronics Manufacturing Co., Ltd., etc.), the thermal conductivity of the sheet obtained is measured by the transient hot-wire method under the following test conditions. (Test conditions) Probe: PD-11 Reference plate: Expanded polyethylene The lower the thermal conductivity of a sheet, the better its thermal insulation properties can be evaluated. For example, if the thermal conductivity of a sheet is 0.060 (W / (m*K)) or less, the sheet can be evaluated as having sufficient thermal insulation properties, although this depends on the application of the sheet.
[0073] The heat resistance of a sheet using hollow resin particles can be evaluated, for example, by the thickness change rate of the sheet in a high-temperature environment. The thickness change rate of the sheet in a high-temperature environment can be determined by the following method. The following description will be given with reference to FIG. 5. First, the sheet (test sheet 30) is processed so that its shape and dimensions are a square with sides of 5 cm. Next, on the plane of the test sheet 30, which is 5 cm square, a central point (D0) and other eight points (D1 to D8) arranged around this central point are set. At this time, when the other eight points (D1 to D8) are connected with the points closest to each other with lines, a square with a side length of 4 cm is formed, which is concentric with the center point (D0) of the test sheet and is one size smaller than the test sheet, and when the center point (D0), one of the four corners (D1, D2, D3, or D4), and the two points closest to these two points (for example, D2 and D8) are selected, and when the points closest to each other are connected with lines, four squares with sides of 2 cm are arranged in a grid pattern. These nine points are selected. Next, the thickness of the sheet at each of these nine positions is measured using a micrometer (for example, MDQ-30, manufactured by Mitutoyo Corporation), and the average value is defined as the average thickness T0 (μm) before heating. Next, the test sheet 30 is heat-treated for 72 hours in a dryer at 120° C. Then, after removing it from the dryer and allowing it to cool naturally, the thickness is measured at the above nine points in the same manner, and the average value is taken as the average thickness after heating T1 (μm). The rate of change in thickness of the sheet in a high-temperature environment is measured based on the following formula (X). Formula (X) ΔT=100×{|T1-T0| / T0} (In the above formula (X), ΔT represents the thickness change rate (%) of the sheet in a high-temperature environment, T1 represents the average thickness (μm) after heating, and T0 represents the average thickness (μm) before heating.) The smaller the thickness change rate ΔT in a high-temperature environment, the more excellent the heat resistance of the sheet is evaluated to be. For example, if the thickness change rate ΔT of a sheet in a high-temperature environment is 8.0% or less, the sheet is unlikely to change in thickness even under high-temperature conditions and can be evaluated to have sufficient heat resistance, although this depends on the use of the sheet.
[0074] The uses of the sheet of the present disclosure are related to the uses of the hollow resin particles described above. Examples of the uses of the sheet of the present disclosure include, but are not limited to, thermal recording sheets and insulating sheets. EXAMPLES
[0075] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. Note that parts and % are by weight unless otherwise specified. The test methods used in the present examples and comparative examples are as follows.
[0076] 1. Manufacturing of hollow resin particles [Example 1] (1) Mixed liquid preparation process First, the following materials (a1) to (d1) were mixed together, and the resulting mixture was used as the oil phase. (a1) 20 parts of methacrylic acid (a2) 30 parts of methyl methacrylate (b) 50 parts of ethylene glycol dimethacrylate (c1) 2,2'-azobis(2,4-dimethylvaleronitrile) (oil-soluble polymerization initiator, manufactured by Wako Pure Chemical Industries, Ltd., trade name: V-65) 3 parts (d1) Cyclohexane 300 parts Next, 4.0 parts of (e) surfactant were added to 800 parts of ion-exchanged water, and the resulting mixture was used as the aqueous phase. A mixture was prepared by mixing the water phase and the oil phase.
[0077] (2) Suspension preparation process The mixture was stirred and suspended using an in-line emulsifying disperser (manufactured by Pacific Machinery Works, trade name: Milder) at a rotation speed of 15,000 rpm to prepare a suspension in which monomer droplets encapsulating cyclohexane were dispersed in water.
[0078] (3) Polymerization process The suspension was stirred for 4 hours in a nitrogen atmosphere at a temperature of 65° C. to carry out a polymerization reaction, thereby preparing a precursor composition containing hollow resin particle precursors encapsulating cyclohexane.
[0079] (4) Solid-liquid separation process The obtained precursor composition was centrifuged with a cooled high-speed centrifuge (manufactured by Kokusan Co., Ltd., product name: H-9R) under conditions of rotor MN1, rotation speed 3,000 rpm, and centrifugation time 20 minutes to dehydrate the solid content. The dehydrated solid content was dried in a dryer at a temperature of 40°C to obtain hollow resin particle precursors containing cyclohexane.
[0080] (5) Solvent removal process The hollow resin particle precursor was heat-treated in air at 80° C. for 15 hours in a vacuum dryer to obtain particles of Example 1. From the results of observation with a scanning electron microscope and the porosity value, it was confirmed that these particles were spherical and had only one hollow portion.
[0081] [Examples 2 to 3] Particles were obtained by the same manufacturing method as in Example 1, except that in the "(1) mixed solution preparation step" of Example 1, the materials and the amounts added were as shown in Table 1. From the results of observation with a scanning electron microscope and the porosity values, it was confirmed that these particles were spherical and had only one hollow part.
[0082] [Example 4] In the "(1) mixed liquid preparation step" of Example 1, the materials and amounts of addition shown in Table 1 were used, and the aqueous phase and the oil phase were not mixed and were subjected to the next "(2) suspension preparation step". Furthermore, in the "(2) suspension preparation step" of Example 1, instead of the suspension method using an in-line emulsifying disperser, a membrane emulsification system (model number: MN-20, manufactured by SPG Techno Co., Ltd.) and a Shirasu porous glass membrane (SPG membrane, diameter 10 mm, length 20 mm, manufactured by SPG Techno Co., Ltd.) with a pore size of 3 μm were used to prepare the suspension by membrane emulsification with the oil phase as the dispersed phase and the aqueous phase as the continuous phase. The particles of Example 4 were obtained by the same manufacturing method as in Example 1. From the results of observation with a scanning electron microscope and the value of porosity, it was confirmed that these particles were spherical and had only one hollow part.
[0083] [Example 5] In the "(1) mixed liquid preparation step" of Example 1, the materials and amounts of addition shown in Table 1 were used, and the aqueous phase and the oil phase were not mixed and were subjected to the next "(2) suspension preparation step". Furthermore, in the "(2) suspension preparation step" of Example 1, instead of the suspension method using an in-line emulsifying disperser, a membrane emulsification system (model number: MN-20, manufactured by SPG Techno Co., Ltd.) and a Shirasu porous glass membrane (SPG membrane, diameter 10 mm, length 20 mm, manufactured by SPG Techno Co., Ltd.) with a pore size of 0.3 μm were used to prepare the suspension by membrane emulsification with the oil phase as the dispersed phase and the aqueous phase as the continuous phase. The particles of Example 5 were obtained by the same manufacturing method as in Example 1. From the results of observation with a scanning electron microscope and the value of porosity, it was confirmed that these particles were spherical and had only one hollow part.
[0084] [Comparative Example 1] In the "(1) mixed liquid preparation step" of Example 1, the materials and additive amounts shown in Table 1 were used, and the aqueous phase and the oil phase were not mixed and were subjected to the next "(2) suspension preparation step". Furthermore, in the "(2) suspension preparation step" of Example 1, instead of the suspension method using an in-line emulsifying disperser, a membrane emulsification system (model number: MN-20, manufactured by SPG Techno Co., Ltd.) and a Shirasu porous glass membrane (SPG membrane, diameter 10 mm, length 20 mm, manufactured by SPG Techno Co., Ltd.) with a pore size of 5 μm were used to prepare the suspension by membrane emulsification with the oil phase as the dispersed phase and the aqueous phase as the continuous phase. The particles of Comparative Example 1 were obtained by the same manufacturing method as in Example 1. From the results of observation with a scanning electron microscope and the value of porosity, it was confirmed that these particles were spherical and had only one hollow part.
[0085] [Comparative Example 2 to Comparative Example 3] Particles of Comparative Examples 2 and 3 were obtained by the same manufacturing method as in Example 1, except that the materials and amounts added were as shown in Table 1 in the "(1) mixed solution preparation step" of Example 1. From the results of observation with a scanning electron microscope and the porosity values, it was confirmed that these particles were spherical and had only one hollow part.
[0086] [Comparative Example 4] First, the following materials (a2), (α1), (α2), (c2) and (d2) were mixed together, and the resulting mixture was used as the oil phase. (a2) 10 parts of methyl methacrylate (α1) acrylonitrile 60 parts (α2) Methacrylonitrile 30 parts (c2) Azobisisobutyronitrile 5 parts (d2) Isopentane 30 parts Next, 200 parts of (y) colloidal silica dispersion (average particle size: 5 nm, effective colloidal silica concentration: 20% by mass) was added to 600 parts of ion-exchanged water. The resulting mixture was used as the aqueous phase. A mixture was prepared by mixing the water phase and the oil phase.
[0087] The mixture was stirred and suspended for 1 minute using a disperser (manufactured by Primix Corporation, product name: Homomixer) at a rotation speed of 4,000 rpm. The resulting suspension was stirred at a temperature of 60° C. for 10 hours to carry out a polymerization reaction.
[0088] After the polymerization reaction was completed, the suspension was filtered and the obtained solid matter was dried at 40° C. in a dryer to obtain thermally expandable microcapsules. 100 parts of the obtained thermally expandable microcapsules were heat-treated in air at 180°C for 3 minutes in a dryer to obtain hollow resin particles of Comparative Example 4. From the results of observation with a scanning electron microscope and the porosity value, it was confirmed that these particles were spherical and had only one hollow part.
[0089] 2. Measurement and evaluation of particles The following measurements and evaluations were carried out for each particle of Examples 1 to 5 and Comparative Examples 1 to 4. The details are as follows.
[0090] (1) Measurement of particle number average particle size, volume average particle size, and particle size distribution The particle size of the particles was measured using a laser diffraction particle size distribution analyzer (Shimadzu Corporation, product name: SALD-2000), and the number average and volume average were calculated, and the obtained values were taken as the number average particle size and volume average particle size of the particles. The particle size distribution was calculated by dividing the volume average particle size by the number average particle size.
[0091] (2) Measurement of particle density and calculation of porosity A. Measurement of apparent density of particles First, 100cm capacity 3 30 cm into a measuring flask 3 The particles were packed in a volumetric flask, and the mass of the packed particles was accurately weighed. Next, the volumetric flask packed with the particles was accurately filled with isopropanol up to the marked line, while being careful not to introduce air bubbles. The mass of isopropanol added to the volumetric flask was accurately weighed, and the apparent density D1 (g / cm 3 ) was calculated. Formula (I) Apparent density D1 = [particle mass] / (100-[mass of isopropanol]÷[specific gravity of isopropanol at measurement temperature])
[0092] A. Measurement of true particle density After crushing the particles in advance, a volume of 100 cm 3 Approximately 10 g of crushed particle fragments were placed in a measuring flask, and the mass of the crushed particle fragments placed was accurately weighed. Then, in the same manner as in the measurement of the apparent density, isopropanol is added to the measuring flask, the mass of isopropanol is accurately weighed, and the true density D2 (g / cm) of the particles is calculated based on the following formula (II). 3 ) was calculated. Formula (II) True density D0 = [mass of crushed particles] / (100-[mass of isopropanol]÷[specific gravity of isopropanol at the measurement temperature])
[0093] C. Calculation of void ratio The apparent density D1 was divided by the true density D0, and the result was multiplied by 100 and then subtracted from 100 to obtain the porosity of the particle.
[0094] (3) Measurement and calculation of shell thickness Twenty hollow resin particles were selected as targets, and their cross sections were observed using a SEM. Next, the shell thickness of each of the 20 hollow resin particles was measured from the SEM images of the particle cross sections. The average of these thicknesses was taken as the shell thickness of the hollow resin particles.
[0095] (4) Amount of volatile organic compounds in hollow resin particles The method for measuring the amount of volatile organic compounds in the hollow resin particles is as follows. Approximately 100 mg of hollow resin particles were placed in a 30 mL screw-top glass bottle and accurately weighed. Then, approximately 10 g of tetrahydrofuran (THF) was placed in the bottle and accurately weighed. The mixture in the glass bottle was stirred with a stirrer for 1 hour to extract the volatile organic compounds (hydrocarbon solvents, etc.) contained in the hollow resin particles. The stirring was stopped, and the resin components of the hollow resin particles that were insoluble in THF were precipitated. A filter (manufactured by Advantec, product name: Membrane Filter 25JP020AN) was attached to a syringe to filter the precipitate to obtain a sample liquid, which was then injected into a gas chromatograph (GC) for analysis. The amount of volatile organic compounds (mass%) per unit mass contained in the hollow resin particles was determined from the GC peak area and a calibration curve created in advance. The detailed analysis conditions are as follows.
[0096] (Analysis conditions) Equipment: GC-2010 (Shimadzu Corporation) Column: DB-5 (Agilent Technologies, Inc.) df=0.25μm 0.25mm ID x 30m Detector: FID Carrier gas: Nitrogen (linear velocity: 28.8 cm / sec) Inlet temperature: 200℃ Detector temperature: 250℃ Oven temperature: increased from 40°C to 230°C at a rate of 10°C / min and held at 230°C for 2 minutes. Sampling volume: 2μL
[0097] (5) Compressive strength of particles The 10% compression strength of the particles was measured using a microcompression tester (MCTM-500, manufactured by Shimadzu Corporation) under the following test conditions. (Test conditions) Indenter type: FLAT50 Objective lens magnification: 50 ·Load speed: 0.8924 mN / sec
[0098] (6) Observation of particle shape 3A is an SEM image of a hollow resin particle of Example 1. FIG. 3B is an SEM image of a cross section of the hollow resin particle of Example 1. The SEM observation conditions were as follows: Scanning Electron Microscope: JEOL, model number: JSM-7610F (Figure 3A) Hitachi, model number: S-4700 (Figure 3B) Acceleration voltage: 2.0 kV (Figure 3A), 5.0 kV (Figure 3B) Magnification: 5,000x (Figure 3A, Figure 3B) These figures confirm that the particles of Example 1 are hollow inside, and that despite being hollow inside, they do not collapse and maintain their spherical shape.
[0099] 3. Sheet manufacturing Using each of the hollow resin particles of Examples 1 to 5 and Comparative Examples 1 to 4, a sheet was produced by the following method. A mixture containing 100 parts of hollow resin particles and 3 parts of polyvinyl alcohol (PVA) was mixed in a 1% by mass aqueous solution of sodium dodecylbenzenesulfonate so that the solid content was 10% by mass. The obtained mixture was applied to a PET film substrate (thickness: 50 μm) whose surface had been corona-treated, using a wire coater. At this time, the amount of the mixture applied was adjusted so that the average thickness of the layer containing the particles only (average thickness not including the PET film substrate) after drying the mixture was 100 μm. The PET film substrate after applying the mixture was dried at 50° C. for 24 hours to produce a multilayer sheet in which a layer containing hollow resin particles was formed on the PET film substrate. This multilayer sheet was used in the following experiments. Hereinafter, the sheets produced using the particles of Examples 1 to 5 and Comparative Examples 1 to 4 will be referred to as sheets of Examples 1 to 5 and Comparative Examples 1 to 4, respectively.
[0100] 4. Measurement and evaluation of the seat The following measurements and evaluations were carried out for each of the sheets in Examples 1 to 5 and Comparative Examples 1 to 4. The details are as follows.
[0101] (1) Measurement of the thermal conductivity of the sheet The thermal conductivity of the sheet obtained was measured by the unsteady thin wire heating method under the following test conditions using a rapid thermal conductivity meter (QTM-500, Kyoto Electronics Manufacturing Co., Ltd.) and thin film measurement software (SOFT-QTM5W, Kyoto Electronics Manufacturing Co., Ltd.). (Test conditions) Probe: PD-11 Reference plate: Expanded polyethylene
[0102] (2) Measurement of thickness change rate of sheet in high temperature environment As shown in Fig. 5, first, the sheet (test sheet 30) was processed so that the shape and dimensions were a square with one side measuring 5 cm. Next, on the plane of this 5 cm square test sheet 30, one central point (D0) and other eight points (D1 to D8) arranged around this one point were set. At this time, when the other eight points (D1 to D8) were connected with the points closest to each other with a line, a square with one side measuring 4 cm was formed that was concentric with the center point (D0) of the test sheet and was one size smaller than the test sheet, and when the center point (D0), one of the four corners (D1, D2, D3, or D4), and the two points closest to these two points (for example, D2 and D8) were selected, and when the points closest to each other were connected with a line, four squares with one side measuring 2 cm were arranged in a grid pattern. These nine points were selected. Next, the thickness of the sheet at each of these nine positions was measured using a micrometer (model number: MDQ-30, manufactured by Mitutoyo Corporation), and the average value was taken as the average thickness T0 (μm) before heating. Next, the sheet was heat-treated for 72 hours in a dryer at 120° C. Then, after removing it from the dryer and allowing it to cool naturally, the thickness was measured in the same manner at the above nine points, and the average value was taken as the average thickness after heating T1 (μm). The thickness change rate of the sheet in a high temperature environment was measured based on the following formula (X). Formula (X) ΔT=100×{|T1-T0| / T0} (In the above formula (X), ΔT represents the thickness change rate (%) of the sheet in a high-temperature environment, T1 represents the average thickness (μm) after heating, and T0 represents the average thickness (μm) before heating.)
[0103] The measurement and evaluation results of each particle and each sheet of Examples 1 to 5 and Comparative Examples 1 to 4 are shown in Table 1 below, together with their raw material compositions.
[0104] [Table 1]
[0105] 5. Discussion The evaluation results of each particle and each sheet will be discussed below with reference to Table 1. As seen from Table 1, the number average particle size of the particles in Comparative Example 1 is 15 μm, the porosity is 80%, and the amount of volatile organic compounds contained is 2.3% by mass. The particles of Comparative Example 1, although made of a resin with a high content of crosslinkable monomer units, have a low compressive strength of 2.2 MPa. As shown in this Comparative Example, particles having a number-average particle size of more than 9.0 μm have a disadvantage in that they are easily crushed when processed into, for example, a sheet, because it is difficult to obtain high compressive strength.
[0106] As seen from Table 1, the number average particle size of the particles in Comparative Example 2 is 2.9 μm, the porosity is 63%, and the amount of volatile organic compounds contained is 3.8% by mass. The particles of Comparative Example 2 have a high thermal conductivity of 0.080 (W / (m*K)). As shown in this Comparative Example, particles with a porosity of less than 70% have poor heat insulation because their thermal conductivity is too high.
[0107] As seen from Table 1, the number average particle size of the particles in Comparative Example 3 is 1.8 μm, the porosity is 74%, and the amount of volatile organic compounds contained is 20.2% by mass. The particles of Comparative Example 3 have a high thermal conductivity of 0.067 (W / (m*K)) and a high thickness change rate ΔT of 28% in a high temperature environment. As shown in this Comparative Example, particles containing more than 5% by mass of volatile organic compounds have poor insulation properties as a result of the thermal conductivity being too high because the volatile organic compounds such as cyclohexane contained in the particles act as a heat transfer medium, and are prone to deformation in a high temperature environment, resulting in poor heat resistance.
[0108] As seen from Table 1, the number average particle size of the particles in Comparative Example 4 is 12.0 μm, the porosity is 86%, and the amount of the volatile organic compound contained is 12.0 mass %. The particles of Comparative Example 4 have a high thermal conductivity of 0.035 (W / (m*K)) and a high thickness change rate ΔT of 35% in a high temperature environment. As shown in this comparative example, particles with a number average particle size exceeding 9.0 μm and containing volatile organic compounds in an amount exceeding 5 mass% are prone to deformation in a high temperature environment and therefore have poor heat resistance. The content of volatile organic compounds in Comparative Example 4 (12.0 mass%) was lower than that in Comparative Example 3 (20.2 mass%), but the particles of Comparative Example 4 contained nitrile group-containing monomer units, and therefore had even worse heat resistance than Comparative Example 3.
[0109] On the other hand, from Table 1, the hollow resin particles of Examples 1 to 5 have a number average particle size of 0.9 to 9.0 μm, a porosity of 74 to 90%, and an amount of volatile organic compounds contained of 0.8 to 3.0% by mass. These hollow resin particles have a high compressive strength of 6.0 MPa or more, a low thermal conductivity of 0.059 (W / (m*K)) or less, and a low thickness change rate ΔT of 7.1% or less in a high temperature environment. Therefore, it has been demonstrated that hollow resin particles having one hollow portion, a number-average particle size of 0.1 to 9.0 μm, a porosity of 70 to 99%, and containing volatile organic compounds of 5 mass% or less have high compressive strength and excellent insulation and heat resistance compared to conventional particles. [Explanation of symbols]
[0110] 1 Aqueous medium 2 Low polarity material 3. Surfactants 4. Monomer Composition 4a Monomer dispersed in an aqueous medium 5. Oil-soluble polymerization initiator 6. Shell 7. Hydrocarbon Solvents 8 Hollow part 10. Micellar 20 Hollow resin particle precursor 30 Test Sheet D0 and D1 to D8 Measurement points on the test sheet 51 Aqueous media 52 Surfactants 53 Monomer Composition 53a Monomer dissolved in aqueous media 54 Water-soluble polymerization initiators 60 Miselle 60a Micelle precursor 100 Hollow resin particles
Claims
1. A sheet containing hollow resin particles, the hollow resin particles have one or more hollow portions, a number average particle size of 0.1 to 9.0 μm, a porosity of 70 to 99%, and an amount of volatile organic compounds contained therein of 5 mass% or less; a repeating unit constituting a resin contained in the hollow resin particle includes a crosslinkable monomer unit, a hydrophilic monomer unit, and a monovinyl monomer unit different from the hydrophilic monomer unit; the crosslinkable monomer unit is at least one selected from the group consisting of a divinylbenzene unit, a divinylnaphthalene unit, a diallyl phthalate unit, an allyl acrylate unit, an allyl methacrylate unit, an ethylene glycol diacrylate unit, an ethylene glycol dimethacrylate unit, a diethylene glycol diacrylate unit, and a diethylene glycol dimethacrylate unit; the hydrophilic monomer unit is a carboxyl group-containing monomer unit, the monovinyl monomer unit comprises at least one (meth)acrylate monomer unit selected from the group consisting of a methyl acrylate unit, a methyl methacrylate unit, an ethyl acrylate unit, an ethyl methacrylate unit, a butyl acrylate unit, a butyl methacrylate unit, a 2-ethylhexyl acrylate unit, a 2-ethylhexyl methacrylate unit, a lauryl acrylate unit, and a lauryl methacrylate unit; the content of the crosslinkable monomer unit is 25 to 59 parts by mass when the repeating unit constituting the resin is 100 parts by mass, The sheet, characterized in that a mass ratio of the carboxyl group-containing monomer unit, which is the hydrophilic monomer unit, to the (meth)acrylate monomer unit, which is the monovinyl monomer unit (carboxyl group-containing monomer:(meth)acrylate), is 60:40 to 20:
80.
2. The crosslinkable monomer unit is at least one selected from the group consisting of a divinylbenzene unit, an ethylene glycol diacrylate unit, and an ethylene glycol dimethacrylate unit, 2. The sheet according to claim 1, wherein the monovinyl monomer unit comprises at least one (meth)acrylate monomer unit selected from the group consisting of a methyl acrylate unit, a methyl methacrylate unit, an ethyl acrylate unit, an ethyl methacrylate unit, a butyl acrylate unit, and a butyl methacrylate unit.
3. The sheet according to claim 1 or 2, having a thermal conductivity of 0.060 W / (m·K) or less.
4. 3. The sheet according to claim 1, which has a thickness change rate of 8.0% or less after heat treatment at 120°C for 72 hours.
5. The sheet according to claim 1 or 2, wherein the hollow resin particles have a 10% compressive strength of 5.0 MPa or more.
6. The sheet according to claim 1, wherein the crosslinkable monomer unit comprises at least one selected from the group consisting of a divinylbenzene unit and an ethylene glycol dimethacrylate unit.
7. 3. The sheet according to claim 1, wherein the hollow resin particles have a particle size distribution (volume average particle size (Dv) / number average particle size (Dn)) of 1.1 to 2.
5.
8. 3. The sheet according to claim 1, wherein the hollow resin particles have a shell, and the shell has a thickness of 0.01 to 1.0 μm.
9. 3. The sheet according to claim 1 or 2, which is a thermosensitive recording sheet.
Citation Information
Patent Citations
Construction material
JP1982027962A
Fish head cutter
JP1986052237A
Production of hollow polymer particle
JP1986087734A
Crosslinked hollow polymer pigment and coating composition using the pigment
JP1990140272A
Method for manufacturing hollow resin particulate, and hollow resin particulate
JP2005054084A